Controllable Hydrodebromination of Tribromomethyl Groups via Lewis Base–Borane-Mediated Ionic and Radical Pathways - Liu, Yan; Phang, Yee Lin; Jin, Ji-Kang; Xu, Wen-Ping; Zhang, Feng-Lian; Wang, Yi-Feng (Synthesis, 2025)
Compounds bearing mono- and dibromomethyl groups are extensively utilized in synthetic and medicinal chemistry. In this regard, selective debromination of readily or easily accessible tribromomethyl compounds offers a direct and efficient method to access those two moieties. In this work, we introduced Lewis base–borane-mediated selective hydrodebromination of tribromomethyl groups via ionic or radical pathway. Using 4-(dimethylamino)pyridine–borane (DMAP-BH3) as a hydride donor, monohydrodebromination of tribromomethyl groups was achieved via nucleophilic substitution by hydride, delivering dibromomethyl groups. On the other hand, treatment of tribromomethyl compounds with an N-heterocyclic carbene–borane (NHC-BH2CN) as a boryl radical precursor in the presence of dilauroyl peroxide (DLP) as radical initiator afforded monobromomethyl compounds through consecutive bromine atom abstractions to cleave two C–Br bonds. Various tribromomethyl group bearing acetamides and acetates were applied in this developed protocol, showcasing good functional group tolerance and broad substrate scope.
Keywords: Lewis base–borane; boryl radical; selective debromination; halogen atom transfer; hydride donor